PELATIHAN ANALISIS DATA DALAM UPAYA PENINGKATAN KEMAMPUAN LITERASI STATISTIK - Elok Fitriani Rafikasari; Risdiana Chandra Dhewy (STKIP PGRI Sidoarjo, 2023)
Statistical literacy is an ability to understand, interpret, and use data-based information to make rational and informational decisions. The purpose of this activity is to improve students' statistical literacy skills. Participants in this training activity were students from PGMI, Hasanuddin Pare Islamic Institute. The stages of the training activities include (1) the presentation of material by the resource person on statistics; (2) Assistance using statistical software with SPSS. At this stage the activity is in the form of providing training on data entry and operation of SPSS software, as well as interpreting SPSS output correctly. Students have the opportunity to ask questions about the operation of the software. At this stage students are expected to be able to operate SPSS software and correctly interpret SPSS output; (3) Discussion and evaluation forums. At this stage it is expected to make a positive contribution so as to increase student interest and learning motivation in statistical data analysis. This data analysis training received a positive response from students. This is evidenced by the active participation of students during the activity. So that with the smooth running of the activities it can be said that the training can be carried out properly and successfully in accordance with the achievement targets.